Invasive plant ecology - Jose, Shibu (CRC Press, 2013)
"Preface Invasion is not a novel phenomenon; however, it is one that has increased tremendously during the past few years due to rapidly expanding trade and transport among countries. It is one of the most important impact humans have ever produced on the earth's ecosystems. In fact, it has led to globalization of world biota, further resulting in biotic homogenization. While some argue that invasion biologists should adopt a more objective and dispassionate stance towards invasive species, everyone agrees that it is a problem that needs attention and action. Recognizing that a deeper understanding of biological characteristics of invasive species and the ecological principles that underpin the invasion process is critical in formulating management decisions, the scientific community has dome an exemplary job in publishing original research as well as synthesis articles on the subject in recent years. Unfortunately, the science is still lagging behind, necessitating a reactive rather than a proactive response to the problem. The body of knowledge is growing so fast, including our ability to predict invasions. This will accelerate the science-based decision making, whether it is for reactive or proactive management or for developing effective public policies. The idea for this book began back in 2009 when the editors organized a regional IUFRO conference on invasive plants in Chandigarh, India. They met again in 2010 at the XXIII IUFOR World Congress in Seoul and finalized the plan for a book that would focus on invasive plant ecology. In addition to selected presentations from the IUFRO conference and the Congress, several prominent authors were invited to contribute chapters on specific topics. In the end, we accepted 18 chapters in the current volume"-- Provided by publisher.
Keywords: Invasive plants -- Control.; Invasive plants -- Ecology.; elektronické knihy; electronic books